2018
DOI: 10.24093/awej/vol9no3.20
|View full text |Cite
|
Sign up to set email alerts
|

The use of L1 as a Source of Humour to Facilitate Interaction in EFL Classrooms

Abstract: The recent decades have witnessed a remarkable increase in the body of research that examine the relationship between humour and language acquisition. This study, however, uses the microanalytical approach of Conversation Analysis (CA) to investigate the impact of the teachers' competent use of the first language (L1) as a source of humour on classroom interaction and, consequently, learning. The turn-by-turn analysis of the data shows how the teacher's use of L1 as a source of humour resulted in smoothness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The positive findings, revealed in CA studies in the Arab context, are promising and encouraging (e.g. [Alghasab, 2017]; [Jawhar, 2018]). Therefore, Arab researchers should be encouraged to discover the connection between CA and EFL learning.…”
Section: Summary Of Evidencementioning
confidence: 82%
See 1 more Smart Citation
“…The positive findings, revealed in CA studies in the Arab context, are promising and encouraging (e.g. [Alghasab, 2017]; [Jawhar, 2018]). Therefore, Arab researchers should be encouraged to discover the connection between CA and EFL learning.…”
Section: Summary Of Evidencementioning
confidence: 82%
“…First, there are studies that cover motivational practices that may contribute to professional development. Al-Nofaie [2017] and Jawhar [2018] exemplified humor as an effective motivational practice that engages learners in interaction and creates learning opportunities. Alkhazraji [2018] identified friendly interaction between teachers and students as a motivational practice that assists grammar learning.…”
Section: Review Of Studies On Pedagogical Interaction In Academic Con...mentioning
confidence: 99%
“…Secondly, teachers utilise L1 to create and enhance interpersonal relationships and express emotions with students by making jokes, or offering students praise and encouragement (Caldwell-Harris, 2014). Teachers' L1 has been shown to be a source of humour which could minimise learners' tension and increase the learners' interactional competence in the classroom (Jawhar, 2018). Importantly, recently it has emerged that the controlled and well-organised use of L1 in EFL classrooms speeds up L2 learning process (Awada et al, 2020); boosts learners' confidence in L2 productive skills (Nilubol, 2020); and lessens the L2 anxiety level (Bukhari & Aziz, 2020).…”
Section: L1 Use In the L2/fl Classroommentioning
confidence: 99%
“…Another study by Jawhar (2018) showed how the appropriate use of L1 as a source of humour yielded an immense amount of interaction from Saudi students at a language institute. She investigated the effect of "the teachers' competent use of the first language (L1) as a source of humour on classroom interaction and, consequently, learning" via using the micro-analytical approach of conversation analysis (CA).…”
Section: Ic Assessment In the Saudi Contextmentioning
confidence: 99%